“We should be able to decide”: Obesogenic factors influencing dietary behaviours of women and adolescents in Ethiopia - Trübswasser, Ursula (Wageningen University & Research, 2022)
Multiple factors can lead to overweight and obesity but unhealthy diets remain one of the key contributors. Diets in turn are influenced by diverse factors. The overall objective of this thesis was to understand the factors influencing dietary behaviours of women and adolescents in low- to middle-income countries, and specifically of adolescents in Ethiopia. Additionally, it aims to explore how these adolescents perceive their food environment and how policies address the different factors of the food environment.